St. Louis Meeting, Oct. 8-13, 1917 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1917)
Iron and steel lire subjects that will receive the attention clue them at the meeting in. St. Louis. Within the past 2 years the smelting of iron ore on a large scale has been started in the St. Louis area, and the blast furnaces are in full operation. Ore is being received. from the Lake Superior region, in large barges .brought clown the Mississippi River. Firebrick, for the lining of the furnaces, is made in the. St. Louis district to a greater extent than elsewhere in the country. At this meeting, there will probably be a discussion of the possibilities of the increase of manganese production in this country, and of improved methods of using it in steel manufacture.